ADGG: Boresha mbari za ng'ombe wa maziwa Tanzania–sehemu ya pili - International Livestock Research Institute (International Livestock Research Institute, 2021)
Part 2 of the African Dairy Genetic Gains (ADGG) project work in improving dairy productivity in Tanzania.